PENGARUH KINERJA LINGKUNGAN TERHADAP FINANCIAL CORPORATE PERFORMANCE DENGAN CORPORATE SOCIAL RESPONSIBILITY DISCLOSURE SEBAGAI VARIABEL INTERVENING - Rahmawati, Ala'; Tarmizi, Achmad (Diponegoro Journal of Accounting, 2012)
The purpose of this study was to examine the influence of Corporate Environmental Performance on Financial Performance (CFP) with the Corporate Social Responsibility (CSR) Disclosure as an intervening variable. Environmental performance is measured using the PROPER (Program Penilaian Peringkat Kinerja Lingkungan Perusahaan) of the Ministry of Environment, CFP measured using the Annual Return, CSR measured using the GRI index. The population in this study is a manufacturing company listed on the Indonesia Stock Exchange (IDX) and participated in PROPER in the year 2009-2011. The research sample is 107 companies, with purposive sampling method of data collection. Types of data used is secondary. Analysis tool used is regression analysis and sobel test. The analysis data technique and hypothesis testing using SPSS software. The results showed that the performance does not significantly positive effect on CFP, Environmental Performance significantly positive effect on CSR Disclosure and CSR Disclosure significantly positive effect on CFP. However, the test results showed that statistically influence the environmental performance indirectly to CFP through CSR Disclosure.